Prototyping Pengendalian Keamanan Ruangan Berbasis Internet of Things (IoT) Menggunakan NodeMCU V3 - Kartarina Kartarina; Miftahul Madani; Made Nugraha Dwitama (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
Securities an safety room are important, creating a sense of security all around. managers of buildings, companies or the environment, employ workers as security officers to be safe from various acts of theft. hiring security personnel is not efficient, because it takes a long time, and it is also tiring. To create room security there are many ways that we can do, one of which is by utilizing technology as a way to maintain security. Internet of Things (IoT) is a very promising technological development to optimize the way with smart sensors and smart devices that work together through the internet network. Data from sensor devices that have been processed can be represented to users through various platforms, one of which is Smartphones with the Android operating system. To build a prototyping of this system, the Message Queue Telemetry Transport (MQTT) communication protocol is used, it takes several tools that are components of the IoT, including a micro controller for example a NodeMCU, which is a relay whose function is as a breaker and current connector, a switch as a door sensors, Selenoid Door Lock as an electronic door lock, and power supply as a power supplier for the entire series built with Web App, rogressive Web App (PWA) technology is a web application development method adopted by Google, making web applications appear as if they can run like native applications on each platform, such as native Android, Windows, Mac, and Linux applications. By building a prototyping of this IoT system, it can help monitor and control the security of doors and windows in the room.